Can Education Compensate Society? The description of a Pedagogical Modality that allows access to differentiated social positions - Giménez, Elena; Navas, Almudena; Graizer, Oscar (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
In this paper we describe the committed pedagogical modality. The study of pedagogic practice is vital to address early school leaving because the production and reproduction of the social and gender orders are initialized in the specialized interactive practices. To get to the description of this modality we have analyzed the pedagogic practice of two teachers, which have been selected from a larger sample, by the type of educational exchanges and pedagogical relationships they establish with the learners. The analysis of your practice we get the data that allow us to identify his work with a way politically compromised, especially with the context in which it is enacted, fact that favours access to alternative social positions. To perform this analysis we have built an instrument used as conceptual tool, based on the Basil Bernstein’s theory and, especially, in the investigations carried out by Morais and Neves (2004). We will explain our use of the bernstenian theory, its relevant concepts, and how they help us to describe the object of study: the committed pedagogical modality. We have conducted this research in two classrooms of a secondary school immersed in a exclusion context; we look at the relationship between academic discourse and the discourse of moral order, and the relationship between teachers and students. The analysis of the relationship between these discourses is remarkable for what it can contribute to the thinking on the pedagogical relation, since it allows us to think about the development and production of training Tools.